ADTU-06 'real world' outcomes of vedolizumab over 12 months: the cross pennine multicentre experience. (8th June 2018) - Selinger, Christian; Levison, Scott; Eliadou, Elenia; Willert, Robert; Carter, Anna; Kemp, Karen; Stansfield, Catherine; Assadsangabi, Arash; Singh, Salil; Crooks, Ben; Tattersall, Suzanne; Hall, Veronica; et al.
Abstract : Background: Vedolizumab (VDZ) is a gut selective α4β7 anti-integrin approved for the treatment of UC and CD. We aimed to assess one year clinical and safety outcomes of VDZ. Methods: We previously reported 12 week outcomes using retrospectively collected demographic, clinical, and adverse effects data of patients treated with VDZ at 8 UK centres since 2014. We now report longer term outcomes, evaluating clinical response at week 12 and 52, using Physician Global Assessment, Harvey Bradshaw Index (HBI) and partial Mayo Score (pMS). Results: Of 203 patients, 135 had CD (96% anti-TNF experienced), and 68 UC (66% anti-TNF experienced). 101 received concomitant immunomodulator therapy and 97 received steroid bridging therapy. Of 135 CD patients, 9 discontinued VDZ prior to week 12. At week 12, 38.5% were in PGA remission and 40.0% had a PGA response. Between week 12 and 52, a further 35 patients discontinued VDZ. At week 52 PGA remission and response were seen in 39.2% and 24.3% respectively. Mean HBI decreased from 9.2 (baseline) to 5.1 (week 12) and 5.2 at week 52 (p<0.01). Of 68 UC patients, 3 discontinued VDZ prior to week 12. At week 12, 48.5% were in PGA remission and 42.6% had a PGA response. Between week 12 and 52, a further 9 patients discontinued VDZ. At week 52, PGA remission and response were seen in 67.2% and 16.4% respectively. Mean pMS decreased from 6.1 (baseline) to 3.1 (week 12) and 2.2 (week 52; p<0.01). Adverse events were reported in 48 cases (24%) Of these 29 were infection related. Overall incidence of infection was 11.1 per 100 person-years of VDZ exposure. Conclusion: In our cohort of refractory (predominantly anti-TNF experienced) patients, VDZ proved to be safe and effective. Although at 12 weeks response/remission rates were similar in CD and UC, VDZ appeared to be more effective at maintaining remission for UC compared to CD. The incidence of infectious complications was lower than that seen with anti-TNF therapies (average 14 per 100 person-years).